Determination of 4-Nonylphenol - Part 1: Optimization of the Gas Chromatographic Determination of 4-Nonylphenol by Orthogonal Array Design and Electronic Pressure Programming - Chee, K.K. (2014)
Journal of Microcolumn Separations